Japan’s Second Kennedy Round (SKR) Program in Indonesia: Case Studies on Shallot and Wheat - Heldi Yunan Ardian; Soesilo Zauhar; Kertahadi Kertahadi (Indonesian Journal of Environment and Sustainable Development, 2014)
Many agricultural assistance programs are provided by local governments and foreign donors. However, even with such active support for agriculture, the impact of the programs still falls short of the expected results. This study focused on shallot and wheat projects in Indonesia funded by Japan’s Second Kennedy Round (SKR) program. A survey was conducted in March 2013; to determine farmers’ perceptions of such projects by observing the following:  the socioeconomic characteristics of the farmers, the farmers’ assessments of the projects benefits and obstacles, and farming feasibility as the comparison and to argue the in-depth interview result. Japan's grant aid through SKR Program claimed by Japanese and Indonesian side, has been effectively implemented resulted from the benefits gained by the underprivileged farmers. However, based on the assessment of farmer’s perception, there are many obstacles faced by the farmer as beneficiaries of the program showed by cross-tabulation analysis and compared by its farming feasibility. Keywords: SKR Program, farmers’ assessments, grant aid